Effect of Vanadium Addition on the Wear Resistance and Rolling Contact Fatigue of Cast Class D Railway Wheels - Samuel Carlos Winiarski; Mário José-Bueno; Ana Cecília de Carvalho; Rodrigo da Silva Miranda; Denilson Santos Monteiro; Andrei Bavaresco Rezende; Noé Cheung; Paulo Roberto Mei (Materials Research, 2025)
Rail transport is one of the main freight transportation modes in Brazil, responsible for transporting about 92% of all extracted ore to ports via railways. However, it incurs high maintenance costs, exceeding $1.5 billion annually, with most of this amount allocated to rolling stock maintenance. This study investigates the influence of vanadium (V) microalloying on the wear and rolling contact fatigue (RCF) performance of cast Class D railway wheels. Using a twin-disc tribometer simulating wheel-rail contact, a vanadium-microalloyed wheel (CD-V) was compared against a conventional wheel (CD). Key parameters evaluated included mass loss, plastically deformed layer thickness, and crack characteristics. While the CD-V wheel showed slightly lower mass loss, the difference compared to the CD wheel was not statistically significant. However, the slightly increased hardness of the CD-V wheel seems to led to greater wear on the rail counterbody, indicating a trade-off. In contrast, vanadium addition demonstrated significant benefits for RCF resistance. The CD-V wheel exhibited a thinner plastically deformed subsurface layer and superior crack morphology, characterized by shorter surface cracks, lower-angle and shallower subsurface cracks. These RCF improvements suggest that vanadium microalloying in cast wheels could offer advantages in operations where shelling resistance is a primary concern.